A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil - de Sousa, Viviane Rodrigues; Couri, Márcia Souto (Zootaxa, 2018)
Liriomyza okrae sp. n. is a new species from Brazil that does not have the yellow thoracic spots usually characteristic of the genus. The specimens were collected in Rondônia state (Brazil), reared from okra—Abelmoschus esculentus (L.) Moench (Malvaceae). Detailed descriptions of adult male, larva and puparium are made, and images of the male, male terminalia, larva, puparium and host-plant are given. A key is provided for Neotropical Liriomyza with an entirely dark thorax.